2003
DOI: 10.1021/ma034892+
|View full text |Cite
|
Sign up to set email alerts
|

Controlled/Living Radical Polymerization of Vinyl Acetate by Degenerative Transfer with Alkyl Iodides

Abstract: Controlled/living radical polymerization of vinyl acetate was achieved by a degenerative transfer process using alkyl iodides as transfer agents. Poly(vinyl acetate) with predetermined molecular weight and relatively low polydispersity was successfully synthesized. Methyl 2-iodopropionate and ethyl iodoacetate were employed as transfer agents, whereas 2,2′-azobis(isobutyronitrile) and R-cumyl peroxyneodecanoate were used as initiators. Methyl 2-iodopropionate and ethyl iodoacetate are both efficient transfer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
186
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(190 citation statements)
references
References 33 publications
4
186
0
Order By: Relevance
“…A similar result was observed in the iodine transfer radical polymerization of VAc. 33,43,[49][50][51] The number-average molecular weights [M n (NMR)] calculated from the -(h=2) and !-end signals (j=2) to the mainchain VAc units (b) was 4100 and 4500, respectively, which were more or less lower than that by SEC [M n ðSECÞ ¼ 5000] based on the polystyrene calibration. The number-average endfunctionality (F n ) obtained from the M n (NMR) and M n (SEC) [F n = M n (SEC)/M n (NMR, -or !-end)] was close to unity for both the -and !-terminals: F n ðÞ ¼ 1:22 and F n ð!Þ ¼ 1:10.…”
Section: Measurementsmentioning
confidence: 99%
“…A similar result was observed in the iodine transfer radical polymerization of VAc. 33,43,[49][50][51] The number-average molecular weights [M n (NMR)] calculated from the -(h=2) and !-end signals (j=2) to the mainchain VAc units (b) was 4100 and 4500, respectively, which were more or less lower than that by SEC [M n ðSECÞ ¼ 5000] based on the polystyrene calibration. The number-average endfunctionality (F n ) obtained from the M n (NMR) and M n (SEC) [F n = M n (SEC)/M n (NMR, -or !-end)] was close to unity for both the -and !-terminals: F n ðÞ ¼ 1:22 and F n ð!Þ ¼ 1:10.…”
Section: Measurementsmentioning
confidence: 99%
“…PMMA with high molecular weights (M n % 80,000) also formed with precise molecular weight control by the addition of 1 or 2 equiv of dimethyl ditelluride (PDI ¼ 1.14-1.18, entries [19][20][21]. As this is a radical reaction, 2-hydroxyethyl methacrylate (HEMA) could also be polymerized in a highly controlled manner in the presence of dimethyl ditelluride without protection of the free hydroxyl group (entries 22 and 23).…”
Section: Applications To (Meth)acrylate Monomersmentioning
confidence: 99%
“…Oka and Tatemoto 18 reported that organoiodine compounds serve as promoters for the controlled polymerization of polyfluorinated vinyl monomers, but their application to other conventional vinyl monomers has had limited success. 19,20 Organoselenium compounds were also used for controlled polymerization under UV irradiation by Kwon et al, 21 but their controllability is insufficient. Takagi et al 22 reported the effect of diphenyl ditelluride on molecular weight control in the 2,2 0 -azobisisobutyronitrile (AIBN)-initiated polymerization of styrene.…”
Section: Introductionmentioning
confidence: 99%
“…However, ITP, OMRP and CoMRP suffer drawbacks of different kinds. Firstly, PVAc derived from ITP undergoes decomposition of the iodide chain end to form an aldehyde [40]. OMRP based on methyl telluride compounds is only efficient to synthesize low molecular weight PVAc owing to the accumulation of low-activity inverted VAc-TeMe adducts during polymerization [28].…”
Section: Introductionmentioning
confidence: 99%